2017
DOI: 10.1007/s11187-017-9971-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation intentions in the entrepreneurial process: concept, empirical findings, and research agenda

Abstract: Prior studies find sizable gaps between entrepreneurial intentions and subsequent actions. We extend models of entrepreneurial intentions by drawing on action phase theory to better understand how entrepreneurial intentions translate into actions. Our study focuses on the effects of implementation intentions on taking entrepreneurial action. The analysis uses two waves of survey data on 422 individuals, from the Swedish general population, who had an explicit interest in starting a business and who reported on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 80 publications
5
112
0
1
Order By: Relevance
“…Using the concepts of a proactive personality and psychological capital as cases of reference, the present study investigates the effects of people's positive psychological attributes on entrepreneurial intentions and actions in the context of a developing country (e.g., Uganda). Secondly, we examined the mediating roles of entrepreneurial intentions and implementation intentions in the relationship between positive psychological attributes and actions (van Gelderen et al, 2018); and the moderating role of perceived family support in the movement from implementation intentions to taking action toward a business start-up. Our analysis F(1, 138) demonstrates that having firm implementation intentions is essential to translating intentions into action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the concepts of a proactive personality and psychological capital as cases of reference, the present study investigates the effects of people's positive psychological attributes on entrepreneurial intentions and actions in the context of a developing country (e.g., Uganda). Secondly, we examined the mediating roles of entrepreneurial intentions and implementation intentions in the relationship between positive psychological attributes and actions (van Gelderen et al, 2018); and the moderating role of perceived family support in the movement from implementation intentions to taking action toward a business start-up. Our analysis F(1, 138) demonstrates that having firm implementation intentions is essential to translating intentions into action.…”
Section: Discussionmentioning
confidence: 99%
“…In support of van Gelderen et al (2018) extended model of entrepreneurial intentions, our findings show that implementation intentions mediate the effects of entrepreneurial intentions on entrepreneurial actions. Implementation intentions involve delegating the behavioral control to situational cues that consequently elicit behavior, making people become more alert to situational cues (van Gelderen et al, 2018). Consequently, people with strong intentions to implement their entrepreneurial ideas become more alert to opportunities for acting on those ideas.…”
Section: Discussionmentioning
confidence: 99%
“…The attitude in this model corresponds to the perceived desirability included in the former model, and behavioral control is a form of perceived viability, considered in the Shapero and Sokol model [44]. Ajzen adds the subjective norm in the second model, which also influences the entrepreneurial intention [72][73][74]. Intention-based models are implemented successfully in social psychology, marketing and management, and prior research revealed very interesting empirical conclusions.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…; Van Gelderen, Kautonen and Fink ; Van Gelderen et al . ). Our study adds to this line of research, and we interpret our findings as providing further evidence for the role of self‐control (Van Gelderen et al .…”
Section: Introductionmentioning
confidence: 97%